Knowledge mapping of severe fever with thrombocytopenia syndrome: a bibliometric analysis - Zhang, Huiying; Zhang, Leiliang (Frontiers in Microbiology, 2024)
Background: Severe fever with thrombocytopenia syndrome (SFTS), caused by the Dabie bandavirus (DBV), formerly known as the SFTS virus (SFTSV), is characterized by rapid progression, high morbidity, and mortality. This study aims to analyze the current research status, hotspots, and trends of SFTS since 2009 through bibliometrics, focusing on original research and providing valuable references and inspirations for future basic research, prevention and control of SFTS. Methods: The Web of Science Core Collection (WOSCC) was used to extract global papers on SFTS from 2009 to 2024. VOSviewer and CiteSpace software were also used to process and visualize results. Results: A total of 760 publications relevant to SFTS were reviewed. Among these publications, the most active country, author, and publication type included China, Liu Wei, and original articles, respectively. Among the institutions, the National Institute of Infectious Diseases emerged as the top publisher. The most frequently used keywords were "China," "Bunyavirus," and "person-to-person transmission." The bibliometric analysis reviewed and summarized the research results in the field of SFTS and demonstrated the research trends in the field. In addition, the study revealed the current research hotspots and predicted the future research frontiers and potential challenges in the field of SFTS, which will provide references for further exploring and investigating the SFTS-related mechanisms and inspire new therapeutic strategies. Conclusions: Bibliometric visualization provides an overview of research advances, hotspots, and trends regarding SFTS and consolidates existing knowledge. SFTS research is in a phase of rapid development, and the number of annual publications in the field is growing steadily and rapidly. This is laying the groundwork for further research and providing new ideas for clinicians engaged in SFTS-related therapies and researchers working to improve public health. Currently, researchers are focused on elucidating the biology of SFTS, exploring antibodies, delving into pathogenesis, and investigating specific therapies.